Is There Infinity? Mathematics, Physics, and Philosophy at Their Crossroads - A Mageed, Ismail (Optimality, 2025)
Since it is at the centre of important philosophical, physical, and mathematical issues, the notion of infinity has attracted interest and caused controversy for millennia. Focusing on its formal existence in mathematics, its debatable presence in physical reality, and the philosophical debates that these different approaches cause, this paper explores the complicated nature of infinity. Crossing these theoretical barriers enables us to better appreciate how the issue Does infinity exist? does not have a single solution, but rather a range of responses depending on the context of inquiry. Though basic to several fields of abstract thinking and scientific hypothesis, the notion of infinity still presents great and ongoing open questions. Most importantly, This paper presents a brief review of important unsolved issues about infinity appearing in the several but connected fields of mathematics, physics, and philosophy. From the ambiguous nature of the continuum of numbers in mathematics to the contradictions of cosmological models in physics and the ongoing discussion about the reality of actual infinities in philosophy, the infinite keeps pushing the limits of human knowledge and the systems we use to understand the world.